Nahsi and Proto-Burnese-Lolo - Bradley, David (2024)
Nahsi (Na-khi in Rock's transcription, formerly called Moso by the Chinese) has been classified as a Loloish language by Shafer and others. Better Nahsi data, from the published works of Rock and of Fu, and further data which clarify Rock's transcription, and elucidate the orthography now used for Nahsi in China, do not support this grouping. While a large proportion of Nahsi vocabulary is plausibly cognate to Proto-Burmese-Lolo (*BL) and Proto-Loloish (°L) forms reconstructed in Bradley 1975, there is only limited systematic regularity of correspondence. Moreover, the tonal and other developments postulated for +BL and 01, by Matisoff are not reflected in Nahsi. It thus seems that Nahsi is very close to 'BL within Proto-Tibeto-;'airman (*TB), but should not be inclu,led within •L. In fact, some similarities between Nahsi and Loloish languagen may be due to areal convergence, e.g. the prenasalized stops, which occur now in adjacent Tibetan, Loloish, and Nahsi languages, but not in other Tibetan or Loloish languages.